THE TEACHER’S CONCEPTION ON SEXUALITY - Freitas, Maria José Dias de (2018)
This is a descriptive study with a qualitative approach and data production through the Focus Group. It wassought to know the conceptions and difficulties of teachers of Kindergarten, Early Childhood Education and Primary Education I, about sexuality in the school environment. The analysis of the data was performed through the Thematic Content Analysis, of the categorical type, which produced two thematic categories. The results pointed out difficulties of the teachers in relation to the theme. The lack of knowledge produces stereotyped information and beliefs, represented in the daily life of the school in the form of prejudice and indifference. The lack of knowledge stems from three factors: deficient formation on the subject, socio-historical constructions and a view of sexuality centered on the adult point of view. The study points out important issues to be included in initial and continuing teacher training.